Sistem Informasi Tugas Akhir Berbasis Web di Jurusan Teknik Informatika Universitas Trisakti - Dwi Yunda; Syaifudin; Syandra Sari (Penerbitan Universitas Trisakti, 2022)
The Department of Informatics has requirements for earning a Bachelor's degree, namely the Final Project. The Final Project is a research paper that must be written for students. However, the process of implementing the final project is still managed manually so problems occur on a regular basis. To avoid further issues, the author conducted research on the Information Systems of the Final Project. This system would not be integrated into the primary system of the university. There was only the Final Project 1 process in the implementation, consisting of a proposal and results seminars. This study aimed to create an Information system of Online Final Project for students who want to take Final Project 1 or those who are taking Final Project 1. This study used the waterfall method which consisted of requirements, design, implementation, and evaluation. In the analysis and design, this study used PHP programming and a MySQL database server. The function test on the application was used to generate the test results. The Final Project Information System application would be used by the admins, students, lecturers (supervisors and examiners), and the final project coordinators.